Milkfish consumption in Central Java, Indonesia - Angunggunanto, Edy Yusuf (1988)
The milkfish (chanos chanos) is a popular food fish in Indonesia, particularly in Java. Milkfish are cultured in brackish water pond, and its culture has been practised for several hundred years. Most of the production is marketed fresh, while the rest are marketed as processed milkfish such as pindang milkfish and presto milkfish. This study aims to examine the consumption patterns and factors that influence the demand for milkfish in Central Java. Milkfish is classified into three types, namely, fresh milkfish, pindang milkfish and presto milkfish. The socio-econanic characteristics of the consume their attitudes and practices and their relative desirability and preferences for milkfish are examined in the study. Results of analysis show that most households consumer fresh milkfish, followed by pindang milkfish and presto milkfish. The fish are usually bought at public markets. On average, consumers buy fresh milkfish four times a month, pindang milkfish about three times a month and presto milkfish once a month. Average quantity bought at each purchase is about 0.6 kilogram. Demand for milkfish is influenced by its own price, price of substitutes, income and size of household. Own price elasticity of demand for milkfish is very high for all type of milkfish. The income elasticity however is less than one but greater than zero.